The impact of emotional intelligence and cultural intelligence on job performance in Russia - Engle, Robert; Dimitriadi, Nikolay; Toskin, Katarzyna (Journal of Management Policy and Practice, 2026)
A great deal of work has been done in recent decades examining the impact of emotional intelligence (EQ) and cultural intelligence (CQ) on extra-role job performance. However, little of this research has used both EQ and CQ constructs together in the same analytical model. In addition, the available literature in is virtually silent with regards to the relationships of these constructs in Russia, a country with a significant multicultural environment. This study examines these relationships, using a sample of 189 supervisory and non-supervisory subjects in Russia. The results suggest that motivational CQ may be seen as an antecedent of CQ and EQ, both of which significantly impact extra-role job performance. EQ and CQ factors were also found to mediate the relationship between motivational CQ and extra-role job performance. In addition, necessary condition analysis was completed adding to model insights. These results extend our knowledge to a Russian sample, and not only support the Thomas et al. (2015) approach to CQ, but also suggest significant implications for current EQ-CQ model theories.
Keywords: Antecedent (behavioral psychology); Cultural intelligence; Emotional intelligence; Job performance; Multiculturalism; Sample (material); dept.bis

An exploratory analysis of equally male/female-owned firm performance in the United States - Toskin, Katarzyna; Jocic, Marko (International Journal of Entrepreneurial Behaviour & Research, 2025)
Keywords: Business performance; Census; Entrepreneurship; Equally male/Female-owned firms; Exploratory analysis; Exploratory research; Family businesses; Firm ownership; Gender; Outcome (game theory); Sample (material); Test (biology); Variance (accounting); dept.bis

Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Achieving quality comfort care in nursing homes and long term care units through ambient assisted living (AAL) environments - Page, Robert; Richardson, Anthony S.; Coppola, Jean (International Journal of Interdisciplinary Research, 2016)
Nursing home administrators are caught in a "perfect storm" of rapidly increasing health care costs, decreasing reimbursement, and increasing competition. This paper documents how these pressures create cascading misalignments resulting in compromises of the quality of comfort care. These problems are inevitable, given the increase in unfunded mandates, where performance evaluation is decoupled from actual performance. Ambient technologies are explored as a means of tracking actual care versus reported care. Independent quality of care tracking and documentation of ambient data, coupled with best practice research and rewards, are explored to promote quality care as a marketing advantage. Implications are discussed.
Keywords: dept.bis; peer-reviewed

Evaluating the Knowledge of Conversational Agents - Park, Mina; Aiken, Milam; Vanjani, Mahesh (Southwestern Business Administration Journal, 2019)
Keywords: dept.bis; dept.mgt; peer-reviewed

College Students Understanding of Production Management and Master Production Schedule through Using a Real World Tool, Complimented with Company Tours and In- Class Visits, Provides an Excellent Learning Experience at Farmingdale State College - O'Sullivan, Jill (Journal of Systemics, Cybernetics and Informatics, 2015)
Manufacturing is playing a significant role in its re-shoring into America. Companies are grappling with ways to obtain that competitive advantage by distinguishing themselves through their intellectual capabilities, process improvements, technology, people, shop floor management and information flows. The purpose of this paper is to describe the effort at Farmingdale State College to educate our students in understanding Production Management and Master Production Schedule (MPS). We are trying to prepare students for entry into the workforce. By using a Real world ERP tool in the classroom while complimenting this learning with touring local manufacturers who use this tool and having production control experts in our classrooms. [1] The opportunity presents itself for these students to visit real world manufacturers using the same tool these students use in the classroom, the Infor Visual ERP. Each semester students go to a local manufacturer to see how the product is made and the ERP system is used to make it. Each semester a subject matter expert, SME, in manufacturing comes into the class and talks about how they use their ERP to perform their functional responsibilities. Students go into these companies and sit down with these Production Manufacturing and IT SME’s to see how they use the modules in their ERP system from estimating, Production Management, MPS to delivery and payment. From the manufacturing window to the Master Schedule Window students learn from these companies SME’s just how they perform their functions, how they use this tool. Then that is replicated this in the classroom lab assignments for students to better understand Production Management, scheduling and work order integrity. They identify the desired schedule (forecast) and populate a Master Production Schedule. They create a BOM with work orders adding operations and material. The Production Management/Control is the function of directing or regulating the movement of goods through the entire manufacturing cycle from the requisitioning of raw material to the delivery of finished products. (APICS Dictionary 13th Edition) The Master Production Schedule is often a major component of Sales and Operations Management. The purpose of the Master Schedule is to translate the Sales forecast into a Production Plan that must be executed by the organization. The Master Schedule is the demand side of the equation and must represent the customers’ needs. In this way the Master Scheduler can give manufacturing its best chance for success. Master Production Schedule (MPS): The MPS should be closely aligned with the Sales Forecast. Students enter a Sales Forecast into the system similar to what they have seen at the companies. Students see how it is the liaison between the Sales Forecast and a production work order. Its function is to translate the Sales Forecast into a viable production schedule that supports the customer requirements, while taking into account shop floor constraints. The MPS must support the Sales Forecast and customer demand. Students learn the importance of this in their lab assignments. They identify and enter shop floor resources. Students learn that companies should never chase supply they should chase demand and manage supply. Supply can mean, purchased parts, and externally produced parts, internally made items, internal machine or labor constraints. The student’s comprehension of this topic, concept and knowledge is significantly enhanced due to the tours to local manufacturers and the individuals that come into the class to discuss these functional areas and the processes they perform in their organizations.

Change Requires Change! Information Technology, Student Preparedness and Industry Collaboration: Supporting the Bridging Process between Education and Training with Innovative Solutions - O'Sullivan, Jill (Journal of Systemics, Cybernetics and Informatics, 2016)
This paper, Change Requires Change: will relate that bridging the gap between education: of what we teach and training: of what industry looks for in prepared skills for students, needs to be relevant to today’s situations. We need to re-evaluate traditional industry academic partnerships which have been relatively successful including; internships, work-study programs, curriculum advisory boards, guest lectures and capstone courses, to identify gaps and opportunities for what is needed to support our future. Do we want to continue with the status-quo or enhance education? Should we be cognizant of emerging trends? What could be the implications on changing academic-industry partnerships? How can we improve? This paper proposes several new approaches to academics and industry practitioner’s towards greater successful collaborations towards student preparation.
Keywords: dept.bis; peer-reviewed

Industry and Academic Partnership leads to Student Driven Success using an innovative Cloud Product in the classroom - O'Sullivan, Jill; Shahrier, Sayem (Journal of Systemics, Cybernetics and Informatics, 2018)
The relationships between Education/Training and Information Technologies at Farmingdale State College are accelerating, with the newest partnership involving the new CloudSuite Industrial Product, CSI, form Infor, USA, Inc. In this arrangement we have a dedicated Intern, Sayem Shahrier, a student at Farmingdale State College who assists with use of the CSI product in the classroom. According to this Intern, the implementation of the Infor CSI tool has been a great real life and hands-on experience. Students in the Education Alliance Program finally received a taste of how an ERP system works. Whether a company is big or small, it should be capable to manage and keep track of all their products and customers in real time. From local companies throughout Long Island all the way up to global mass markets have utilized the Infor CSI tool and have taken customer data to further maximize not only on profits but improve on operational excellence, customer intimacy, and the manufacturing process. Using this innovative tool and this partnership synergy, makes our students best prepared for industry entry and successes. This partnership brings together researchers and practitioners to support the bridging process between Education/Training and Information Technologies.
Keywords: dept.bis; peer-reviewed

Data mining and social networking sites: protecting business infrastructure and beyond - Bassett, Richard; Chamberlain, Tiffany; Cunningham, Stephen; Vidmar, Gregor (Issues in Information Systems, 2010)
Keywords: dept.bis; peer-reviewed

Sustainable Revenue Strategies for Enterprise Computing Solution Providers - Bassett, Richard A. (Research Yearbook, 2012)
Keywords: dept.bis; peer-reviewed

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Undergraduate Business Analytics and the Overlap with Information Systems Programs - Ceccucci, Wendy; Jones, Kiku; Toskin, Katarzyna; Leonard, Lori (Information Systems Education Journal, 2020)
As companies continue to put data and business analytics as their top priority, universities will need to supply students with the appropriate skill sets that meet this demand and offer future opportunities to their graduates. Although business analytics is a new field, many of the required competencies stem from already established areas such as Information/Computer Technology or Information Systems. Using a sample of 225 randomly selected AACSB accredited business schools this study examined the new developments in Business Analytics undergraduate academic programs, and determined the amount of overlap between the Business Analytics and the Information/Computer Technology degree programs. Our findings reveal that approximately 36 percent of the Business Analytics programs overlap with the Information/Computer Technology programs. In addition, the top three required courses in most Business Analytics programs include a Database course, predictive analytics course, and Introduction to Business Analytics. This research provides valuable insight for schools that haven't adopted a Business Analytics degree yet or are looking to improve their existing curriculum. In addition, colleges and universities can now utilize the appropriate Information Systems courses and include them as important foundation and part of their Business Analytics programs.
ERIC Number: EJ1258206
Keywords: Business Administration Education; Business Schools; College Curriculum; Computer Science Education; Elective Courses; Information Technology; Required Courses; Undergraduate Study; dept.bis; peer-reviewed; ⛔ No DOI found

Information Technology Work Value Differences - Toskin, Katarzyna; McCarthy, Richard V. (Journal of Computer Information Systems, 2021)
This study investigates reasons behind high employee turnover of IT professionals through the value placed on intrinsic, extrinsic, leisure, and social rewards. It addresses two questions; what are the most preferred work values by IT professionals, and how do they differ from other professions. Data was collected via a survey using subjects from Amazon Mechanical Turk. A sample of 380 respondents was used. Key findings reveal that intrinsic rewards were the most important work values for IT professionals followed by leisure, extrinsic, and social rewards. Furthermore, when compared to the preferences of non-IT professionals, the levels of preferences for intrinsic rewards were statistically significantly higher for IT professionals than all other professions. This study provides valuable insight regarding key motivating factors of IT professionals and offers practical implications for practitioners relating to job characteristics that are most likely to reduce IT turnover and rethink their rewards systems.
_eprint: https://doi.org/10.1080/08874417.2019.1639567
Keywords: IT employee motivation; Information technology; dept.bis; peer-reviewed; turnover; work values

Flow through Regression: A Guide to Interpreting and Communicating Regression Models for Data Analytics Students - Toskin, Katarzyna; Kunene, Niki (Information Systems Education Journal, 2021)
Faculty teaching data analytics at undergraduate level are often faced with the tension created by student under-preparedness, the demands of the course, and time constraints. How do faculty close this gap? In this paper, we propose the use of flow diagramming as an accessible method for interpreting regression analyses, in ways that are time efficient and not alienating to the student. Our study shows that the use of such flow diagrams has a positive effect on student understanding without additional remedial instruction. Time saved can be directed at core learning objectives of the analytics.
ERIC Number: EJ1319909
Keywords: Business Administration Education; College Faculty; College Preparation; Data Analysis; Pretests Posttests; Remedial Instruction; Statistics Education; Teaching Methods; Time Management; Undergraduate Students; Visual Aids; dept.bis; peer-reviewed; ⛔ No DOI found

Emotional and Cultural Intelligences' Impact on Extra-Role Job Performance in Russia - Engle, R. L; Dimitriadi, N.; Toskin, K (International Business: Research, Teaching, and Practice, 2021)
Keywords: dept.bis; ⛔ No DOI found

An Approach for Ushering Logistic Regression Early in Introductory Analytics Courses - Kunene, Niki; Toskin, Katarzyna (Information Systems Education Journal, 2022)
Logistic regression (LoR) is a foundational supervised machine learning algorithm and yet, unlike linear regression, appears rarely taught early on, where analogy and proximity to linear regression would be an advantage. A random sample of 50 syllabi from undergraduate business statistics courses shows only two percent of the courses included LoR. Conceivable reasons for this dearth of LoR content is likely related to topic complexity, time constraints, and varying degrees of tool ease of use and support. We propose that these constraints can be countered by: [1] introducing logistic regression early, [2] informed tool selection prioritizing ease of use with comprehensive output, and [3] using/developing innovative, accessible, and easy to understand concept learning aids. This approach would leverage the proximity to linear regression and probability readily embed distributed practice for student understanding of a foundational technique.
ERIC Number: EJ1363423
Keywords: Business Administration Education; Comparative Analysis; Concept Formation; Course Content; Course Descriptions; Goodness of Fit; Institutional Characteristics; Introductory Courses; Private Colleges; Probability; Regression (Statistics); State Universities; Statistics Education; Teaching Methods; Two Year Colleges; Undergraduate Students; Universities; Usability; dept.bis; peer-reviewed; ⛔ No DOI found

Impact of emergent technologies on US workforce: exploratory analysis. - Toskin, Katarzyna (Journal of Information Systems Applied Research, 2023)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

The Evolving Landscape of International Consumer Data Privacy Compliance. - Pisano, Mark; Smith, Robert A.; Badr, Kauther S. (ACET Journal of Computer Education & Research, 2022)
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Using a Multilingual Chatbot for Foreign Language Practice. - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Issues in Information Systems, 2020)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

The Unintentional Risk or Liability of Implementing Deploying, or Adopting a Private Blockchain Network - Pisano, Mark; Bassett, Richard (ACET Journal of Computer Education and Research, 2021)
Keywords: dept.bis; peer-reviewed; ⛔ No DOI found

Organizational Cost and Complexity Saving Opportunities via the Development, Deployment, and Implementation of Blockchain Networks - Pisano, Mark; Bassett, Richard (Information Technology and Management Science, 2021)
Blockchain is being promoted as the platform to disrupt business as usual in many transaction-heavy sectors. Questions remain about the future standards of blockchain, their feature set, functionality, and the willingness of organisations to disrupt their existing revenue streams via blockchain. The most significant near-term promise that affords industry is the cost and complexity savings via the standardization of their technology infrastructure stacks. This paper explores the benefits available of reduced costs and complexity via the adoption of blockchain.
Number: 1
Keywords: Blockchain; banking; deployment; dept.bis; human capital; industries; peer-reviewed

Property Management – An Industry of Fragmented Technology Solutions - Bassett, Richard; Pisano, Mark (Information Technology and Management Science, 2022)
Successful property management, which can be done by individual owners or by professional property managers, has numerous interrelated complex business processes: tenant attraction, screening, leasing, tenant move-in, property maintenance, retention/lease renewals, tenant move-out, and reputation management. Property managers must be highly skilled communicators and thoroughly understand the legal implications of housing and contract law in their operating environments. The lack of affordable solutions available to small and mid-sized property managers drives their use of fragmented technology solutions provided by numerous technology vendors that employ redundant data-gathering methods, putting them at a competitive disadvantage. This research paper explores the information systems needs of property managers in contrast to the solutions available to them in the marketplace.
Number: 1
Keywords: Automated business process; dept.bis; fragmented technology solutions; peer-reviewed; property leasing; property management; property marketing

Entrepreneurial Women of Jazz: An Historical, Multidisciplinary Investigation. - Oppedisano, Jeannette M. (2008)
Keywords: dept.bis; faculty_collection; sabbatical_report

Teaching tip GetVirtual: A universal service-based learning framework - Toskin, K.; Pisano, M.A.; Corey, T. (Journal of Information Systems Education, 2023)
This paper introduces a universal framework for service-based learning which provides information systems students with opportunities to gain invaluable hands-on experience. More specifically, through this framework, students can develop hard, soft, and interdisciplinary skills in preparation for their first professional careers upon graduation. In addition to introducing the framework, we provide student testimonials and feedback as well as lessons learned from our experience in efforts to prepare and help other schools interested in offering similar growth opportunities to their students to have a smooth and successful implementation. © 2023, Journal of Information Systems Education. All Rights Reserved.
Keywords: Experiential learning & education; Framework; GetVirtual; Service-learning; Teaching tip; dept.bis; peer-reviewed; ⛔ No DOI found

An economic model of machine translation - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2021)
1 citations (Crossref) [2023-10-31]
Keywords: dept.bis; peer-reviewed

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed

Chatbots for Multilingual Conversations - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Journal of Management Science and Business Intelligence, 2019)
Chatbots emulate human dialogue to provide a more intuitive user interface to applications or simply provide entertainment. Chatbots rely on technology to function and new and emerging technologies such as NLP (Natural Language Processing) and AI (Artificial Intelligence) can be used to increase the ability of chatbots to emulate a more natural and free flowing conversation. As more and more mobile device users transition to increased use of texts and messaging chatbots can be used to provide consumers with multilingual support and services. While some chatbots have been developed in other languages, currently most converse only in English, and only a few can communicate in multiple languages. If configured correctly multilingual chatbots have the potential of providing a digital communication option that transcends language barriers. For our research we focused on the use of a chatbot that links the English-speaking Tutor Mike system with Google Translate, thus providing conversational capability in 103 languages, which is more than any other artificial multilingual agent is currently capable of. Two humans communicated with the system using German, Spanish, and Korean, and a group of undergraduate students reviewed the English translations of the chatbot’s replies. Results show that the responses from German and Spanish were cogent and natural, but those from Korean were less understandable. As a caveat, Asian languages lack much of the linguistic nuances of European languages. For example, there may be no plural form or gender in the Asian language. Unlike German where nouns and adjectives constantly change endings depending on what they are doing in a sentence and, unlike Spanish, which have numerous verb conjugations, Asian languages require no such changes. This might impact the translation ability and quality of a multilingual chatbot. Additional research and enhancements can improve chatbots used for European to Asian language translations and vice-versa. Regardless, our research shows promising results in the future use of multilingual chatbots to allow communication across the globe with business potential in the use of such chatbots to provide customer service and online live interaction with customers across the world.
Keywords: Chatbot; Multilingual; Communication; Machine Translation; dept.bis; dept.mgt; peer-reviewed

Automated translation preference with a bilingual chatbot - Park, Mina; Aiken, Milam (International Journal of Computers & Technology, 2019)
Free, online language translation services are being used by people around to the world to facilitate communication. However, it takes time and effort for a person to load the Web page in a browser, copy and paste text into the site, and translate words. The process quickly becomes tiresome. Instead, some computer programs are providing automated translation. However, no studies have been conducted to determine the efficiency or effectiveness of such an approach. In this study, we compare how students used an English-based chatbot with and without German automatic translation. Results show that students took nearly 1.5 times longer than their stated upper time limit to manually translate. In contrast, the automated translation was at least 30 times faster. In addition, the students were significantly more satisfied with the automated than the manual system.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00215 tex.type: [object Object]
Keywords: Chatbots; Google Translate; Tutor Mike; artificial conversation; dept.bis; dept.mgt; machine translation; peer-reviewed

A Study on Cloud Computing Adoption Within Small and Mid-Size Businesses (smbs) - Richardson, Anthony; Mate, Geoffrey (International Journal of Interdisciplinary Research, 2018)
A growing number of organizations have difficulty scaling-up their IT infrastructure to handle their growing needs and increased resource demands. Digital Technology Platforms (DTPs) have been identified by Gartner, Inc. as one of the top 10 strategic technology trends of 2017. While DTPs may be mainstream and easily adopted by large enterprise-sized organizations, there is an opportunity for such platforms within Small and Mid-Size Businesses (SMBs). The bottom line is that computing and server hardware is expensive for SMBs. Furthermore, it may be difficult for SMBs to assess and price the labor and resources needed for a company to have acceptable performance while controlling costs. The purpose of this paper is to examine how cloud computing technologies are adopted by SMBs and the respective drivers associated with costs and capability that may reduce costs for an organization. This paper explores how four variables – Robust Capability, Limited Capability, Cost Constraint, and Resource Abundance interact to impact the adoption of DTPs within SMBs. Adopters of DTPs are classified as Efficient, Proactive, Resistive, and Reactive. With respect to adoption efficacy, a model is proposed for assessing the capability and resource readiness as correlated to SMB adoption of DTPs. A study of 12 SMBs and the implementations of DTPs is presented and posited with the proposed adoption model. Due to the extensive investments required in procuring infrastructure services –adoption enablement is imperative for SMB-sized organizations to realize a return on investment. Implications are discussed.
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

How do humans interact with chatbots?: an analysis of transcripts - Park, Mina; Aiken, Milam; Salvador, Laura (International Journal of Management and Information Technology, 2018)
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-012-207-389-604 tex.type: [object Object]
Keywords: dept.bis; dept.mgt; peer-reviewed